Evalution the Effects of Raloxifene and Risedronate on Serum Biochemical Markers - Abdurrahman Yeter; Vural Kavuncu; Fatma Deniz Evcik; Ümit Seçil Demirdal; Volkan Subaşı; Tuncay Çakır (Galenos Yayinevi, 2014)
Objective: Osteoporosis a progressive bone disease that is characterized by a decrease in bone mass which can lead to an increased risk of fracture. Osteoporosis is still a global public health problem. In recent years, many new osteoporosis drugs have become available but none of them is totally curative. The aim of the present study was to evaluate and compare the effects of risedronate and raloxifene on bone mineral density (BMD) and bone turnover markers. Materials and Methods: A total of ninety patients with postmenopausal osteoporosis were randomly divided into three groups receiving calcium-vitamin D plus raloxifene, calcium-vitamin D plus risedronate, and only calcium-vitamin D (control group). Serum osteocalcin and collagen type 1 cross-linked C-telopeptide (CTX) were measured before treatment and after 3, 6, 9 and 12 months of treatment. BMD was measured by Dual-Energy X-Ray absorptiometry (DEXA) before treatment and after 12 months of treatment. Results: Serum CTX levels were decreased significantly (p<0.001) in all groups from baseline to post therapy of 3 months and this decrease continued to the end of the study. Serum osteocalcin levels were decreased significantly (p<0.001) in treatment groups compared to control group. L1-L4 and femur total BMD was statistically lower in treatment groups compared to control group after 12 months of the therapy (p<0.001 and p<0.05, respectively). Conclusion: The results of the present study showed us that risedronate and raloxifene were both effective on bone mineral density and the effect of both of them to do not differ not from each other in the treatment of osteoporosis. (Turkish Journal of Osteoporosis 2014;20: 110-6)